If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(p+3)=-14
We move all terms to the left:
7(p+3)-(-14)=0
We add all the numbers together, and all the variables
7(p+3)+14=0
We multiply parentheses
7p+21+14=0
We add all the numbers together, and all the variables
7p+35=0
We move all terms containing p to the left, all other terms to the right
7p=-35
p=-35/7
p=-5
| -6x+2=-5x+4 | | 12b+10=11b-4 | | 3/5+g=3/10 | | 3x-2/x+4=8 | | Y=3.5x×37-60 | | 12b+10=7b-4 | | √2x+100-√x-1=9 | | 4x+31=2+5x | | Y=3.5x(37)-60 | | 50x10-2x20/4=0 | | 4(x+1)+1-x=10+x | | -10n*2+35n=0 | | 24+6x=8x+8 | | 396=(13+x)(17+x) | | 2y=12.30 | | -h/4=1.5 | | (x+93)+(2x)=180 | | (x+93+(2x)=180 | | 0=1x^2+36x-288 | | P+x+90=180 | | 80=4(v-76) | | 1/4x=1.5x | | -44(6y-12)=-2y | | b-98/1=1 | | 3(u+8)-8u=34 | | .4n=16 | | 15=23-4q | | v+36=26 | | 71=20+3r | | 127.5=4.25*b | | X+2y=12.30 | | 20(7g+-47)=40 |